Minimally Invasive Cavity Preparation by Bridging the Gap Between Conservation and Effectiveness - Shazia Shaikh; Tayyaba Akram; Bakhtawar Bhagil; Aleena Ali; Mehwish Munawar; Amira Shahid; Aneesa Khalid (Pakistan Journal of Medicine and Dentistry)
Background: Minimally invasive cavity preparation (MIC) is an evolving restorative technique aimed at preserving sound tooth structure while ensuring effective caries removal. This study aimed to assess the effectiveness of minimally invasive cavity preparation in terms of patient comfort, restoration success, and post-operative sensitivity by comparing it to the conventional cavity preparation method.